High throughput platform to explore RNA–protein interactomes. (2nd January 2016) - Sutandy, F. X. Reymond; Hsiao, Felix Shih-Hsiang; Chen, Chien-Sheng
Abstract: RNA binding proteins (RBPs) and RNA interaction is an emerging topic in molecular biology. Many reports showed that such interactions contribute to many cellular processes as well as disease development. Several standard in vitro and in vivo methods were developed to fulfill the needs of this RBP–RNA interaction study to explore their biological functions. However, these methods have their limitations in terms of throughput. In this review, we emphasize two important high throughput methods to studying RBP–RNA interactions, affinity purification and protein microarray. These methods have recently become robust techniques regarding their efficiency in systematically analyzing RBP–RNA interactions. Here, we provide technique overviews, strategies and applications of these methods during biological research. Although these technologies are just beginning to be explored, they will be most important methods in this study.